2003
DOI: 10.1080/0144361031000098352
|View full text |Cite
|
Sign up to set email alerts
|

A 27-year review of obstetric hysterectomy

Abstract: A retrospective case-review of 52 mothers who had a peripartum hysterectomy over the past 27 years was conducted at the Rotunda hospital, Dublin, Ireland. The chief indications were uncontrollable haemorrhage due to rupture of the uterus, placenta praevia and uterine atony. Obstetric hysterectomy is a formidable operation, usually performed as a life-saving measure and requires expert surgical dexterity in order to minimise the significant morbidity. The benefits of the subtotal operation appear to be superior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 10 publications
1
7
1
1
Order By: Relevance
“…The incidence of 0.14% in this series compares favorably with other reported incidences (3, 7). However, it is higher than those reported in the recent literature (4), (8–12). There are many factors affecting the incidence of obstetric hysterectomy, such as placental disorders, ruptured uterus, uterine atony, intrauterine death, various sites of infection, uterine fibroids, and disseminated intravascular coagulopathy (13–16).…”
Section: Discussionsupporting
confidence: 68%
“…The incidence of 0.14% in this series compares favorably with other reported incidences (3, 7). However, it is higher than those reported in the recent literature (4), (8–12). There are many factors affecting the incidence of obstetric hysterectomy, such as placental disorders, ruptured uterus, uterine atony, intrauterine death, various sites of infection, uterine fibroids, and disseminated intravascular coagulopathy (13–16).…”
Section: Discussionsupporting
confidence: 68%
“…No difference was detected in the volume of blood products transfused between the two groups. Smaller retrospective studies have produced conflicting results when comparing subtotal and total hysterectomy 11,13–15 . The results of this large, national study would suggest no difference in the outcomes between women managed with the two different operations.…”
Section: Discussionmentioning
confidence: 82%
“…The proportions of women undergoing total and subtotal hysterectomy were approximately equal. Studies and guidelines have suggested that subtotal hysterectomy is a preferable operation because of a lower degree of haemorrhage and speed of operation, 10,11 although some authors have recommended a total hysterectomy to be certain of achieving haemostasis 12 . It is perhaps surprising that the proportion of women undergoing total hysterectomy was so high.…”
Section: Discussionmentioning
confidence: 99%
“…Hysterectomy occurs in 0.2 to 5/1000 births and is commonly associated with cesarean delivery with risks reported to be 10-to 20-fold higher in cesarean as compared with vaginal deliveries. [28][29][30] Bowel injury is associated with adhesions and is more common with prior surgery. Urinary tract injuries occur in 1 to 2/1000 deliveries and are more common in cesarean as compared with vaginal deliveries.…”
Section: Risks Maternal Short-term Risks Of Cesarean Deliverymentioning
confidence: 99%